2021
DOI: 10.1093/ndt/gfab042
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of kidney biopsies in hospitalized patients with COVID-19, acute kidney injury and/or proteinuria

Abstract: We report a multicentric retrospective case series of patients with COVID-19 who developed acute kidney injury and/or proteinuria and underwent a kidney biopsy in the Paris and its metropolitan area. Forty-seven patients (80.9% men) with COVID-19 who underwent a kidney biopsy between March 08 and May 19, 2020 were included. Median age was 63 years IQR [52–69]. Comorbidities included hypertension (66.0%), diabetes mellitus (27.7%), obesity (27.7%), history of chronic kidney (25.5%), cardiac (38.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 38 publications
2
83
0
5
Order By: Relevance
“…Virus detection (using immunohistochemistry for SARS-CoV-2 nucleocapsid and RNA in situ hybridization) were negative in patient samples on which it was performed. Another series from France demonstrated tubular injury in the most severely ill cohort whereas glomerular pathology was restricted to the non-ICU patients 34 . Of note, most biopsies were performed several weeks after the onset of COVID-19 symptoms, and most have failed to show notable SARS-CoV-2 infection of the kidney.…”
Section: Pathophysiology Of Covid-19 Akimentioning
confidence: 99%
See 2 more Smart Citations
“…Virus detection (using immunohistochemistry for SARS-CoV-2 nucleocapsid and RNA in situ hybridization) were negative in patient samples on which it was performed. Another series from France demonstrated tubular injury in the most severely ill cohort whereas glomerular pathology was restricted to the non-ICU patients 34 . Of note, most biopsies were performed several weeks after the onset of COVID-19 symptoms, and most have failed to show notable SARS-CoV-2 infection of the kidney.…”
Section: Pathophysiology Of Covid-19 Akimentioning
confidence: 99%
“…In addition, these clinical data should be integrated with pathological findings from analyses of kidney biopsy samples 29 33 to gain greater insights into the pathophysiology of COVID-19 AKI. Evidence from a study of biopsy data from 47 patients in France demonstrated that kidney injury seen in cases with the most severe respiratory disease in the ICU is predominantly tubular (66.7%); by contrast, collapsing glomerulopathy and focal segmental glomerulosclerosis were not seen in critically ill patients but were observed in 70.6% of cases not in the ICU 34 . More than two coexisting comorbidities were seen in over 60% of cases and the occurrence of collapsing glomerulopathy correlated highly with the expression of high-risk APOL1 genotypes.…”
Section: Features Of Covid-19 Akimentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney biopsies may give some clues. Direct virulence of SARS-CoV-2 may be responsible for kidney involvement with acute tubular injury and podocytopathies [21,22,23]. In a report of kidney biopsies in COVID-19 patients, podocytopathies and tubulo-interstitial diseases were main ndings while immune mediated glomerular diseases were also found [24].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney involvement is frequent in COVID-19, as more than 40% of cases have abnormal proteinuria at hospital admission (16,17). Scarce histological data are available, showing in most cases ATN, collapsing glomerulopathy or TMA in patients with acute COVID-19 infection (18)(19)(20)(21)(22). AKI is also common during MIS-C, ranging from 10% to 60% of the cases (6, 23, 24) while it was described in four adults in a case series of 20 MIS-A with cardiac involvement (12).…”
Section: Discussionmentioning
confidence: 99%